2012
DOI: 10.1007/s00423-012-0963-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of medical treatment and care: are surgeons’ working conditions and job satisfaction associated to patient satisfaction?

Abstract: This study demonstrates strong associations between surgeons' working conditions and patient satisfaction. Based on these findings, hospital managements should improve work organization, workload, and job resources to not only improve surgeons' job satisfaction but also quality of medical treatment and patient satisfaction in Surgery departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 78 publications
2
40
0
Order By: Relevance
“…Our results are in line with similar findings in German surgeons, where enhanced psychosocial work stress was linked to lower quality of care [12,8]. The observed associations contribute to increasing evidence of adverse work conditions in the hospital and their impact on medical performance and suboptimal care, which results in reduced patient safety [12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are in line with similar findings in German surgeons, where enhanced psychosocial work stress was linked to lower quality of care [12,8]. The observed associations contribute to increasing evidence of adverse work conditions in the hospital and their impact on medical performance and suboptimal care, which results in reduced patient safety [12].…”
Section: Discussionsupporting
confidence: 91%
“…We suggest system-based, i.e., organizational and work-design interventions that address the reciprocity of effort and reward in the workplace. This is of particular interest within the clinical context, where high job demands and detrimental working conditions lead to increasing resignation in physicians and jeopardize patient safety [8,24,11,12]. This could be achieved through reducing effort and work demands, while simultaneously improving reward in the hospital workplace.…”
Section: Implications Of the Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Targeted interventions specific for the healthcare context may be better able to protect worker psychological health and the benefit of supporting healthcare staff safety is two‐fold, because the notion that the health of the worker is related to the well‐being of their patients has already been established (Halbeslben et al, ; Hall et al, ; Mache et al., ; Seki & Yamazaki, ). Numerous intervention strategies and job redesign approaches have been raised (e.g., Bodenheimer & Sinsky, ), including; more efficient use of team members for administration; expanding roles in multi‐disciplinary teams to permit certain professions to more efficiently distribute responsibilities and; co‐location of multi‐disciplinary team members to increase efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Research on healthcare workers has demonstrated that there is a relationship between excessive job demands, limited resources and adverse health outcomes (Gilles, Burnand, & Peytremann‐Bridevaux, ; Lavoie‐Tremblay, Trépanier, Fernet, & Bonneville‐Roussy, ). The consequences of poor working conditions are not only limited to the health of workers, as links can be drawn between adverse health outcomes in healthcare professionals and their provision of quality care in terms of patient safety incidents (Halbeslben, Wakefield, Wakefield & Cooper, 2008; Hall, Johnson, Tsipa & O'Connor, ), and the likelihood of near‐miss errors (Seki & Yamazaki, ) and even the job satisfaction of surgeons is related to patient satisfaction (Mache, Vitzthum, Klapp, & Groneberg, ). All of these working conditions and job factors are inter‐linked, and evidence suggests that these can be explained by the Psychosocial Safety Climate (PSC) model.…”
Section: Introductionmentioning
confidence: 99%